Genetic diversity and pathogenicity of Sphaceloma rosarum (teleomorph Elsinoe rosarum) causing spot anthracnose on roses - Bagsic, I.; Linde, M.; Debener, T. (Wiley, 2016)
Roses produced or grown in the field, as well as pot‐grown and cut roses, are attacked by different fungal pathogens causing leaf spot diseases. The incorrect identification and scoring of these pathogens and the lack of information about their genetic and pathotype diversity hamper resistance breeding. This is especially true for the hemibiotrophic ascomycete Sphaceloma rosarum, which is often confused with other fungi. Here for the first time, the genetic variability between isolates at both the molecular and morphological level is analysed. Eighty leaf spot samples were collected from different rose genotypes at five different locations, and 15 single conidial isolates established. All of the samples showed high morphological similarities to the reference isolate CBS 213.33 that was obtained from a public repository. By sequencing a part of the large subunit (LSU) of the 28S ribosomal RNA and phylogenetic analysis, high sequence similarities were shown to other Sphaceloma species for 13 of the isolates and the CBS reference. One of the isolates clustered with Septoria species and another clustered with Seimatosporium species. UPGMA clustering with 145 polymorphic AFLP markers resulted in five distinct groups in the majority rule consensus tree for the 14 S. rosarum isolates, including the CBS reference. Jaccard similarities ranged from 0·31 to 0·91. A detached leaf assay using a differential set of five rose genotypes led to the classification of the five tested isolates as five distinct pathotypes. Therefore, grouping depending on the avirulence gene diversity was clearly different from clustering using selectively neutral AFLP markers that were evenly distributed throughout the genome.